2022
DOI: 10.1073/pnas.2111445119
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and natural killer cell imbalances prevent muscle stem cell–mediated regeneration following murine volumetric muscle loss

Abstract: Significance Skeletal muscle is one of the largest tissues in the body and can regenerate when damaged through a population of resident muscle stem cells. A type of muscle trauma called volumetric muscle loss overwhelms the regenerative capacity of muscle stem cells and engenders fibrotic supplantation. A comparison of muscle injuries resulting in regeneration or fibrosis revealed that intercellular communication between neutrophils and natural killer cells impacts muscle stem cell-mediated repair. P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 93 publications
(115 reference statements)
5
31
0
Order By: Relevance
“…5a, d-f). These RFP - NADH + cells probably included neutrophils, resident macrophages, and fibro/adipogenic progenitors (FAPs), which could regulate MuSCs functionally, but the density of FAPs increased much more slowly than infiltrating neutrophils which peaked around 24 hpi 7,8,10,28,35,76,77 . Therefore, we reasoned that most RFP - NADH + cells observed were neutrophils; next, we performed immunostaining in the whole-mount TA muscle using fluorophore-conjugated antibodies of neutrophils (Gr-1 and Ly6G) and found that more than 85% of NADH + cells were Gr-1 + or Ly6G + in Injured-GC and Injured-GC mice at 1.5 dpi (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5a, d-f). These RFP - NADH + cells probably included neutrophils, resident macrophages, and fibro/adipogenic progenitors (FAPs), which could regulate MuSCs functionally, but the density of FAPs increased much more slowly than infiltrating neutrophils which peaked around 24 hpi 7,8,10,28,35,76,77 . Therefore, we reasoned that most RFP - NADH + cells observed were neutrophils; next, we performed immunostaining in the whole-mount TA muscle using fluorophore-conjugated antibodies of neutrophils (Gr-1 and Ly6G) and found that more than 85% of NADH + cells were Gr-1 + or Ly6G + in Injured-GC and Injured-GC mice at 1.5 dpi (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…5a, d-f). These RFP -NADH + cells probably included neutrophils, resident macrophages, and fibro/adipogenic progenitors (FAPs), which could regulate MuSCs functionally, but the density of FAPs increased much more slowly than infiltrating neutrophils which peaked around 24 hpi 7,8,10,28,35,76,77 .…”
Section: The Interaction Between Rfp + /Rfpnon-myogenic Cells and Act...mentioning
confidence: 99%
See 1 more Smart Citation
“…While much of the current clinical understanding arises from functional data and observations from those injured ( Mase et al, 2010 ; Garg et al, 2015 ; Dziki et al, 2016 ); our knowledge of the pathophysiology and mechanisms of failed regeneration has emerged from rodent and porcine models ( Corona et al, 2016 ; Greising et al, 2019 ) which is paramount to the development of new technologies for transplant sources. Two aspects of the pathophysiology of the muscle at the initially VML injury site are vital to understanding, developing and evaluating treatments; 1) the lost muscle at the primary injury site (i.e., the local muscle environment after injury), failed regeneration, pathological fibrosis ( Corona et al, 2020 ), chronic and heightened inflammation ( Larouche et al, 2022 ), and altered force transmission and muscle architecture ( Goldman et al, 2021 ); and 2) progressive secondary injury to non-injured muscle and systemic insults such as motor neuron axotomy ( Corona et al, 2018 ), denervation ( Sorensen et al, 2021 ), and metabolic inflexibility ( Dalske et al, 2021 ). Multiple potential therapeutic targets exist because the functional deficit is not solely due to the loss of muscle tissue, however, skeletal muscle transplantation near the time of injury could both improve function and prevent the progressive, secondary injury.…”
Section: Current Research Gaps: Pathophysiologic Impact Of Volumetric...mentioning
confidence: 99%
“…Although Ly-6G, an anchored surface protein implicated in tissue neutrophil extravasation, is the most widely used marker to recognise mouse neutrophils by immunohistology [82], both mouse and human neutrophils have also been identified in the literature with antibodies against Ly-6B2 or enzymes contained in their granules, such as MPO (Table 2), albeit never in dystrophic muscles.…”
mentioning
confidence: 99%